ACCURACY OF SHEAR WAVE ELASTOGRAPHY IN THE DIAGNOSIS OF HEPATIC FOCAL LESIONS - SHAHZAD , MA; MUSHTAQ , S; MASOOD , H; MASOOD , D; AHMED , R (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to evaluate the accuracy of Shear Wave Elastography (SWE) in diagnosing hepatic focal lesions using triphasic CT as the gold standard. The study was conducted prospectively at the Department of Radiology, Nishtar Medical Hospital, from January 2022 to January 2023. Patients with at least one hepatic focal lesion ranging from 1 to 5 cm in diameter were included in the study. All patients underwent SWE scanning and ultrasound examination. The segment of focal lesions was evaluated, and 5-8 measurements were taken for quantitative analysis of stiffness. In patients with multiple focal lesions, the pathology of all lesions was confirmed by MRI and CT, and the most accessible lesion was analyzed. The mean of all measurements was compared with the findings of triphasic CT and tumor markers to estimate SWE's accuracy, specificity, and sensitivity. The study was conducted on 100 patients, of which 85 were males and 17 were females. The mean stiffness in benign lesions was 10.4 ± 6.32 kPa, and in malignant lesions was 16.3 ± 9.24 kPa. This difference was statistically significant (P<.002). A cutoff value 13.25 was used to differentiate between malignant and benign lesions. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of SWE were 78.05%, 71.43%, 88.9%, 52.3%, and 64.3%, respectively. The mean tissue stiffness in focal fatty infiltration was 12.7 ± 8.9 kPa, and in hemangioma lesions was 9.6 ± 4.3 kPa. The mean stiffness in HCC was 15.5 ± 7.1 kPa, in cholangiocarcinoma was 32.6 ± 8.26 kPa, and in metastatic lesions was 22.2 ± 0.5 kPa. In conclusion, SWE has a high sensitivity, specificity, and accuracy for differentiating malignant and benign hepatic focal lesions. The study shows that the stiffness of benign and malignant lesions differs significantly.